PENGOLAHAN LIMBAH AMPAS TAHU MENJADI KUKIS OLEH KADER POSYANDU KELURAHAN BALANGNIPA - Ishak, A.Taufik; Srimularahmah, Andi; Asfar, Andi Muhammad Irfan Taufan; Asfar, Andi Muhammad Iqbal Akbar; Asis, M. Nasrul; Handayani, Firti (Bahasa Indonesia, 2023)
Industrial by-products, are industrial wastes or industrial by-products, which are produced during the production process of an industry but are not the desired main product. Components or materials that occur as a natural result of industrial processes and often have no commercial value or can even be considered as waste. One of the industrial wastes is tofu dregs. Tofu dregs is a by-product of the process of making tofu for other soy products. When soybeans are processed to produce tofu, the soybean seeds are soaked, ground, and extracted to obtain soy milk. This soy milk is then further processed into tofu, while the tofu dregs become waste. In Balangnipa Village, there are 4 operating tofu industries which produce tofu dregs which is only made or used as animal feed, whereas tofu dregs can be used as a product in the form of cookies. The lack of public knowledge of tofu dregs waste processing is the basis for this service. So that with this service it will help the community in the implementation of making cookies through the stages of counseling, training and mentoring to partners. The results of this program are able to increase partners' knowledge in processing tofu waste into cookies. The results of this program are able to increase partners' knowledge and productivity in processing tofu waste into cookies is packaged 250 gram pouch. Abstrak Hasil samping industri, adalah limbah industri atau produk sampingan industri, yang dihasilkan selama proses produksi suatu industri tetapi tidak merupakan produk utama yang diinginkan. Komponen atau material yang muncul sebagai hasil alami dari proses industri dan sering kali tidak bernilai komersial atau bahkan dapat dianggap sebagai limbah. Salah satu limbah hasil industri adalah ampas tahu. Limbah ampas tahu adalah hasil samping dari proses pembuatan tahu produk kedelai lainnya. Ketika kedelai diolah untuk menghasilkan tahu, biji kedelai tersebut direndam, digiling, dan diekstraksi untuk mendapatkan susu kedelai. Susu kedelai ini kemudian diproses lebih lanjut menjadi tahu, sementara ampas tahu menjadi limbah. Di Kelurahan Balangnipa terdapat 4 industri tahu yang beroperasi yang menghasilkan limbah ampas tahu yang hanya dibuata atau dijadikan pakan ternak padahal limbah ampas tahu dapat dijadikan produk berupa kukis. Kurangnya pengetahuan masyarakat akan pengolahan limbah ampas tahu menjadi hal yang mendasari pengabdian ini. Sehingga dengan aadanya pengabdian ini akan membantu masyarakat dalam pelaksanaan pembuatan kukis melalui tahap penyuluhan, pelatihan dan pendampingan kepada mitra. Hasil dari program ini mampu meningkatkan pengetahuan mitra dalam mengolah limbah ampas tahu menjadi kukis. Hasil program ini mampu meningkatkan pengetahuan mitra dan produktifitasnya dalam mengolah limbah ampas tahu menjadi kukis dengan kemas pouch 250 gram.